Kajian Produktivitas Alat Gali Muat dan Alat Angkut dari Pit 1 untuk Pengangkutan Batu Granit di PT Aditya Buana Inter Desa Jurung Kecamatan Merawang - Eko Eko Pryatna Gaol; Janiar Pitulima; Alfitri Rosita (MINERAL, 2019)
The mining industry sector is an important sector for Indonesia's development (Prasetya and Ernest, 2013). PT Aditya Buana Inter, hereinafter abbreviated as PT ABI, is one of the mining companies that utilize natural resources in the form of rock mining (article 34) Law No. 4 (2009), in this case granite and began mining activities in 2002. The main activities in granite mining consist of stripping the overburden, drilling, blasting, dismantling, loading and transporting to the processing unit (crushing plant) with the distance from the mining front to the processing unit namely ± 1.7 km. Area of ​​40 Ha Mining Business Permit is located in Jurung village. The granite mining activities carried out by PT ABI are carried out with an open-pit mining system. Based on the PT ABI work plan for the production target of transporting granite in January 2018 is 13,000 BCM, while the actual production is only 9,085 BCM with unattainable 3,915 BCM. The percentage of granite stone production reaches 69% of the work plan target. The cause of not achieving the production target value set by PT ABI can be influenced by several factors, one of which is the ineffective amount of work time wasted. ncreased work efficiency is done by making improvements to avoidable obstacles so that the working efficiency of the loading and excavating tool has increased from 75% to 78% and transportation equipment from 70% to 77.6% with production to 11,139 BCM. Addition of transportation equipment for 1 unit match factor so that it reaches the target of 13,000 BCM